-2(d+6)=0

Simple and best practice solution for -2(d+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(d+6)=0 equation:


Simplifying
-2(d + 6) = 0

Reorder the terms:
-2(6 + d) = 0
(6 * -2 + d * -2) = 0
(-12 + -2d) = 0

Solving
-12 + -2d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -2d = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -2d = 0 + 12
-2d = 0 + 12

Combine like terms: 0 + 12 = 12
-2d = 12

Divide each side by '-2'.
d = -6

Simplifying
d = -6

See similar equations:

| 3a-4.5=4.8 | | m/8=5/12 | | X=x+22 | | 3x-57=-5x+15 | | 6/3/4= | | -6m^2+23m+4=0 | | 3s-6+2w=-2+w | | 3(3a-1)-2=-32 | | 3x-57=-5x+115 | | a(3+x-2b)=c(dx-2) | | -7x+10(x-6)=9(3x+4) | | (X-2)+(3x-7)+(5x)=180 | | -n(5n+8)+8(n+2)= | | 8+y^2=2*16 | | -2+m=20 | | -8(v-3)-4v=120 | | 9x^2-18xy-8x+16y= | | 10x-20+7=12+6x+3 | | -5.6+8a=7a+7.6 | | -8-(-16+10)=12 | | 7x(1-4x)+5(1+2x)= | | (x^2+6x+5)+(x^2+6x+5)= | | 6x-4=16+2x | | 3/2x-y=17 | | 4m-4=rm | | 2x-6=3x+1-x-6 | | x-3/2y=13 | | -13=8m+5m | | X+(x-1)+(x+1)=90 | | 2v+3=19 | | 3(-4x)=-2(6x-9) | | 3(y-4)-4=2y+6.9 |

Equations solver categories